Protótipo portátil para analisar sementes por biospeckle laser: validação e desenvolvimento - Vicentini, Bruno (2023)
The technique called Biospeckle Laser (BSL) consists of using a dynamic speckle laser for determining and/or evaluating the activity level in biological material. The analyzes carried out using the BSL technique are based on the lighting of the material to be studied, using an optical apparatus installed in instrumentation and/or optical physics laboratories. Some limitations for its uses outside the laboratory are: mechanical vibrations, external light interference, and the volume occupied in a traditional setup. In order to carry out this analysis in the field, a miniaturized equipment was developed, which is, a portable prototype to analyze seeds. The objective of this work was to validate this portable prototype developed to execute the BSL technique in the field, comparing the results of the analyzes of viable and artificially aged soybean seeds, carried out in a traditional laboratory setup and in the portable prototype. It was also intended to propose constructive and ergonomic improvements that contribute to the improvement and development of this prototype.